iBook by using Apple's bonjour protocol in a wireless classroom - Siti Balqis, Idris (2012)
The purpose of this project is to provide the way of solution for teachers and students nowadays in Malaysia especially the primary schools students. Students especially in the primary schools have to carry their heavy backpacks and can cause serious health problems. This paper will be focusing one-Textbook by using Apple's Bonjour Protocol in a Wireless Classroom.